Sizing and scarring of whale shark (Rhincodon typus Smith, 1828) in the Cenderawasih Bay National Park - Yusup A Jentewo; Roni Bawole; Tresia S Tururaja; Mudjirahayu Mudjirahayu; Zeth Parinding; Hendrikus R Siga; Muhammad Dailami; Abdul Hamid A Toha (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
This study aims to determine the total length and scar condition of the body of whale sharks (Rhincodon typus) in Cendrawasih Bay National Park (TNTC), Papua-Indonesia. Photo-identification was used to identify individuals of the whale shark R. typus based on spot patterns behind the last gill slit of each individual. Photo-identification was also used to determine the scar of the whale shark. The total length of whale sharks were estimated based on the length of a snorkeller (assumed to be 1.6 m) swimming alongside the whale shark. We identified 21 individuals of R. typus. Of these 21 individuals, 14 were new sightings and seven were re-sightings that have been recorded in the previous photo collection database. R. typus ranged in size from 2 to 5 m total length (average 3.78 m, ±0,86, N= 21). Based on their size, all individuals of whale shark were categorized as juvenile. 52% of R. typus identified had scars and 38 % were not and 10% were unknown. The majority of whale sharks had amputation (12 individuals) and abrasion (7 individuals) scars. Scars occurred most often on the caudal fin and dorsal fin, five and four individuals respectively. This information is useful for understanding potential threats and designing better management programmes for R. typus conservation in TNTC. Abstrak Penelitian ini bertujuan untuk menganalisis panjang total dan kondisi luka hiu paus (Rhincodon typus) di Taman Nasional Teluk Cendrawasih (TNTC), Papua-Indonesia. Identifikasi foto digunakan untuk menentukan identitas individu hiu paus berdasarkan pola bintik di balik celah insang terakhir masing-masing individu. Identifikasi juga menggunakan foto berdasarkan luka hiu paus. Panjang tubuh total hiu paus diperkirakan berdasarkan panjang seorang perenang snorkel (diasumsikan 1,6 m) yang berenang bersama hiu paus. Kami mengidentifikasi 21 individu hiu paus, 14 individu diantaranya adalah hiu paus baru, sedangkan tujuh individu lainnya merupakan hiu paus yang pernah tercatat dalam database koleksi foto sebelumnya. Hiu paus berukuran panjang total 2 sampai 5 m (rata-rata 3,78 m, ± 0,86, N = 21). Berdasarkan ukurannya, semua individu hiu paus termasuk dalam kategori yuwana. Sebanyak 52% dari hiu paus yang diidentifikasi memiliki luka, 38% tidak memiliki luka dan 10% tidak teridentifikasi. Mayoritas hiu paus memiliki bekas luka potong (12 individu) dan luka lecet (tujuh individu). Lokasi luka paling sering terjadi pada sirip ekor dan sirip punggung, masing-masing lima dan empat individu. Informasi ini berguna untuk memahami potensi ancaman dan untuk merancang program pengelolaan yang lebih baik untuk konservasi R. typus di TNTC.